AgeWell.de - study protocol of a pragmatic multi-center cluster-randomized controlled prevention trial against cognitive decline in older primary care patients - Zülke, Andrea; Luck, Tobias; Pabst, Alexander; Hoffmann, Wolfgang; Thyrian, Jochen René; Gensichen, Jochen; Kaduszkiewicz, Hanna; König, Hans-Helmut; Haefeli, Walter E.; Czock, David; Wiese, Birgitt; Frese, Thomas; et al. (BMC geriatrics, 2019)
In the absence of treatment options, the WHO emphasizes the identification of effective prevention strategies as a key element to counteract the dementia epidemic. Regarding the complex nature of dementia, trials simultaneously targeting multiple risk factors should be particularly effective for prevention. So far, however, only few such multi-component trials have been launched, but yielding promising results. In Germany, comparable initiatives are lacking, and translation of these complex interventions into routine care was not yet done. Therefore, AgeWell.de will be conducted as the first multi-component prevention trial in Germany which is closely linked to the primary care setting.